Myxoinflammatory Fibroblastic Sarcoma of the Parotid Gland: First Case Report and Literature Review - Wei, Changhong; Yang, Xuejia; Guo, Pingping; Chen, Xiaoyu; Li, Chunjun; Chen, Jun; Zhou, Sufang (Frontiers in Medicine, 2022)
Myxoinflammatory fibroblast sarcoma (MIFS) is a rare, low-grade malignant soft tissue tumor. Most of the previously reported cases about this tumor were diagnosed within the soft tissues. Here, we report a unique case of myxoinflammatory fibroblast sarcoma (MIFS) of the right parotid gland in a 39-year-old Chinese male. The tumor primarily consisted of an inflammatory area and a mucus-like area in a migratory distribution. A number of lymphocytes, neutrophils, viral-like cells with large nucleoli and eosinophilic cytoplasm or Reed-Sternberg-like cells, as well as spindle cells and epithelial-like aberrant cells were observed within the tumor. They only expressed Vimentin protein and no other specific immunohistochemical markers. The various cytomorphology and immunohistochemical features of this tumor were highly consistent with MIFS found in other sites. Therefore, several leading pathologists finally confirmed the final diagnosis of MIFS in the right parotid gland after repeated deliberation. To our knowledge, this is the first case of MIFS occurring in the parotid gland, and therefore, our study might provide a novel basis for the tumor biological behavior in MIFS and allow us to better understand the pathology of this rare tumor.